Physics Teachers' Opinions on Algodoo Training - Gökhan Sontay; Orhan Karamustafaoğlu (Universitas Pendidikan Indonesia, 2023)
The purpose of this research is to reveal the feelings and thoughts of physics teachers towards Algodoo training within the scope of the 4005 TUBITAK project named Innovative and Technology Supported Applications in Physics Education. This study was carried out with phenomenological research within the context of the qualitative research approach. The study group of the research consisted of 22 physics teachers trained in the 4005 TUBITAK project and volunteered to participate in the research. Data were obtained from semi-structured interviews. The data were carried out following the descriptive analysis method with the help of the NVivo 9 program. As a result of descriptive analysis, four categories emerged. These are the installation and application of the Algodoo program, physics teaching activities, and apps similar to Algodoo and Algodoo training. Based on the findings obtained from the research, it was concluded that most of the teachers were very interested in using Algodoo in their lessons, could benefit from Algodoo in their lessons, and could prepare simple physics simulations. Based on the results, Suggestions such as disseminating Algodoo training with in-service training for teaching physics subjects with interactive applications were presented to those interested in the subject.